Promoting Diversity in Otolaryngology Residency Programs: Underrepresented in Medicine Funding for Visiting Medical Student Electives - Audrey M. Abend; Shaila T. Man; Li‐Xing Man (OTO Open, 2025)
Abstract Objective This study aims to report the prevalence and characteristics of underrepresented in medicine (URiM) funding for visiting medical student clerkships in Otolaryngology–Head and Neck Surgery (OHNS) residency programs in the United States. Study Design Manual online review of Accreditation Council for Graduate Medical Education (ACGME)‐accredited OHNS residency programs as of January 2024, reflective of typical medical student search methodology. Setting An online review. Methods For each program, at least 2 authors captured presence of funding, the funding amount, funding origin, and eligibility criteria. Presence and amount funding were analyzed for possible associations with program type (by FREIDA™ program description), urbanization level, cost of living, and degree of racial and ethnic diversity in the program's geographic location. Results Of 131 programs, 49 (37.4%) offered URiM funding, primarily through diversity, equity, and inclusion (DEI) entities (67.3%) or OHNS departments (32.7%). Mean funding per 1‐month rotation was $1908. Eligibility criteria varied, with 63.2% using a non‐specific URiM definition and 18.4% following the Association of American Medical Colleges definition. Funding presence did not differ by geographic region (P = .06), program type, urbanization level, or cost of living. However, funding amounts varied significantly by region (P < .01) and were significantly different between programs in diversity index 35.0% to 44.9% versus 45.0% to 54.9% and 55.0% to 64.9% (P = .007 and P = .002, respectively). Conclusion URiM funding is available in a minority of OHNS programs, with substantial variability in funding amount and eligibility criteria. Standardized guidance on defining URiM eligibility may benefit students and institutions. Funding may correlate with local racial and ethnic diversity, warranting further research.